1993
DOI: 10.1086/173360
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal Measure of the Solar Magnetic Field

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 0 publications
3
52
0
1
Order By: Relevance
“…This conclusion is consistent with the previous result by Lawrence, Ruzmaikin, & Cadavid (1993). The degree of intermittency (the interval of allowed h) of the magnetic field in an active region increases as the flaring activity rises.…”
Section: Calculations Of Structure Functions For Eight Active Regionssupporting
confidence: 93%
“…This conclusion is consistent with the previous result by Lawrence, Ruzmaikin, & Cadavid (1993). The degree of intermittency (the interval of allowed h) of the magnetic field in an active region increases as the flaring activity rises.…”
Section: Calculations Of Structure Functions For Eight Active Regionssupporting
confidence: 93%
“…Earlier attempts to do this have indicated a high degree of scale invariance (Lawrence et al 1993(Lawrence et al , 1996Cadavid et al 1994;Stenflo & Holzreuter 2002, 2003aJanßen et al 2003;Pietarila Graham et al 2009), which is characteristic of a multi-fractal. Our discovery of a magnetic dichotomy, however, suggests a scenario in the spatially unresolved domain that has similarity with the idealized 2-component model, with the flux split into two discrete states, a collapsed and an uncollapsed state, each with well separated distribution functions, one concentrated around high field strengths (of order 1 kG), the other peaked at zero field strength.…”
Section: Discussionmentioning
confidence: 99%
“…The fractal dimension of a multifractal set is the maximum fractal dimension of the fractal subset that comprise the multifractal (Mandelbrot 1983). Numerous studies have revealed the multifractality of solar ARs, but also of the Quiet-Sun magnetic fields (e.g., Lawrence, Ruzmaikin, and Cadavid 1993;Cadavid et al, 1994;Lawrence, Cadavid, and Ruzmaikin 1996;Abramenko et al, 2001;Abramenko et al, 2002).…”
Section: Solar Magnetic Fieldsmentioning
confidence: 99%